Effect of heating time on the nutritional value of sap during traditional brown sugar processing from Arenga pinnata - Maryani, Yeyen; Rochmat, Agus; Jayanudin; Kurniawan, Teguh (Asia-Pacific Journal of Science and Technology, 2020)
Investigation of the contents of palm sugar is very important to study the quality of the sugar that comes from Lebak in Banten province, Indonesia. In this study, the nutritional value of the sap was analysed every 30 min during the traditional production of Arenga palm sugar. The content of the simple sugars sucrose, glucose and fructose was analysed during the heating of Arenga sap through application of high performance liquid chromatography. Analysis of the mineral content, i.e. of iron (Fe), zinc (Zn), copper (Cu) and manganese (Mn), was performed through application of atomic absorption spectrometry. The antioxidant activity was determined by application of the ferric reducing antioxidant power assay. The results showed that there was a change in composition of sucrose and fructose in palm sap to sucrose, glucose and fructose in palm sugar. Glucose and fructose content during the production process decreased. However, the sucrose content increased. The highest sucrose content was observed at 90 min of heating, which was 90.35% of all constituent saccharides. Regarding mineral content, Fe was the most abundant, and was found to be present at a level of 132.39 mg/kg at 90 min. The highest antioxidant capacity of 179.99 mg of ascorbic acid/kg sample was observed after 90 min of heating during palm sugar production.